2021
DOI: 10.1158/1078-0432.ccr-21-1625
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Castration-Resistant Prostate Cancer in ctDNA during Sequential Androgen Receptor Pathway Inhibition

Abstract: Purpose: Cross-resistance renders multiple lines of androgen receptor (AR) signaling inhibitors increasingly futile in metastatic castration-resistant prostate cancer (mCRPC). We sought to determine acquired genomic contributors to cross-resistance. Experimental Design: We collected 458 serial plasma cell-free DNA samples at baseline and progression timepoints from 202 patients with mCRPC receiving sequential AR signaling inh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 45 publications
4
88
0
Order By: Relevance
“…TF for WES was estimated using manually fitted ploidy models for copy number and heterozygous SNP deviation, as described previously. 25…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TF for WES was estimated using manually fitted ploidy models for copy number and heterozygous SNP deviation, as described previously. 25…”
Section: Methodsmentioning
confidence: 99%
“…Targeted DNA sequencing was performed on all samples using an established targeted panel capturing the exons of 73 prostate cancer-relevant genes, according to the published methodology. [23][24][25] Whole-exome sequencing (WES) was performed on 28 tumor samples (and matched gDNAs) using the same protocol as for targeted DNA sequencing except that hybridization capture was carried out with the Roche Nimblegen SeqCap EZ MedExome kit. A detailed description of somatic and germline mutation calling and copy number evaluation is given in the Data Supplement.…”
Section: Dna Sequencing and Variant Detectionmentioning
confidence: 99%
“…In castration‐resistant disease, AR gene amplification is the dominant genomic mechanism contributing to increased AR expression 11,14 . More recently, whole genome sequencing has helped define the existence of a critical transcriptional enhancer 600−700 kb upstream of the AR gene body, with coamplification of both the AR gene body and associated enhancer representing the most common genomic pattern observed in mCRPC clinical samples 13,15,20–22 …”
Section: Overview Of Ar Genotype In Prostate Cancermentioning
confidence: 99%
“…Another study exploiting dynamic ctDNA analysis to monitor genetic evolutions during ensartinib treatment in NSCLC showed that TP53 mutations promoted tumor evolution and accelerated occurrence of resistance, thus indicating TP53 mutations at baseline were independently correlated with worse clinical outcomes [87]. Deep targeted and whole-exome sequencing of ctDNA in metastatic castration-resistant prostate cancer patients for comparison of base-line and posttreatment showed that the dominant androgen receptor (AR) genotype continues to evolve during sequential lines of AR inhibition and drives acquired resistance [88].…”
Section: Detection Of Ctdna Mutations For Cancer Monitoring and Assessment Of Minimal Residual Diseasementioning
confidence: 99%